1996
DOI: 10.1046/j.1537-2995.1996.36696269512.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for undertransfusion

Abstract: Red cell and platelet transfusions were appropriately ordered for all patients who met the transfusion criteria. Undertransfusion is not a problem at this institution according to the criteria established. It is recommended that other institutions expand their blood utilization audits to include investigation for evidence of undertransfusion. Further research regarding the issue of undertransfusion is warranted and could be expanded to include other components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…There is a paucity of studies of undertransfusion, with only two previous studies reported to our knowledge. The first by Mair and colleagues evaluated all patients at a single center in Florida that had a hemoglobin (Hb) concentration below 7 g/dL or platelet (PLT) count of fewer than 10 × 10 9 /L over a 3‐month period. Of the 55 patients identified, all but eight had received a transfusion, and of those eight all had appropriate reasons for nonadministration of transfusion.…”
mentioning
confidence: 99%
“…There is a paucity of studies of undertransfusion, with only two previous studies reported to our knowledge. The first by Mair and colleagues evaluated all patients at a single center in Florida that had a hemoglobin (Hb) concentration below 7 g/dL or platelet (PLT) count of fewer than 10 × 10 9 /L over a 3‐month period. Of the 55 patients identified, all but eight had received a transfusion, and of those eight all had appropriate reasons for nonadministration of transfusion.…”
mentioning
confidence: 99%
“…Indeed, as stated above, to our knowledge none of the authors who have addressed undertransfusion found that it actually was significant because they all used extremely restrictive definitions: Mair, Hb less than 7 g/dL; Hibbs, Hb less than 6 g/dL; Saxena, Hb less than 5 g/dL . These thresholds seem quite low for the general population and all the more inadequate for the oldest old.…”
Section: Discussionmentioning
confidence: 97%
“…To date, the main comparable studies have explored undertransfusion. However, they were carried out in the general population with restrictive definitions of the term . On the contrary, no publication has addressed the insufficient administration of RBC in this specific population, which due to its age and vulnerability is less likely to tolerate transfusion thresholds that are too restrictive.…”
mentioning
confidence: 99%
“…The relative rarity of identifiable undertransfusion has been reported previously in two other studies. One study examined 55 patients with Hb levels of less than 7 g/dL or PLT counts of fewer than 10 × 10 9 /L . No cases of undertransfusion were found.…”
mentioning
confidence: 99%
“…One study examined 55 patients with Hb levels of less than 7 g/dL or PLT counts of fewer than 10 3 10 9 /L. 19 No cases of undertransfusion were found. The second study used a Hb of 5 g/dL and a similar PLT threshold.…”
mentioning
confidence: 99%